FACTORS INFLUENCING MILLENNIALS’ AND ZILLENNIALS’ DECISIONS ON HAJJ SAVINGS OWNERSHIP IN WEST JAVA - Wiiasih, Ranti; Nurhayati (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
Hajj is one of the pillars of Islam that must be performed if one is able. This ability includes physical and material abilities. However, currently the waiting period for Hajj reaches decades, so there is a need for financial planning for the millennial and zillennial generations, one of which is through Hajj savings. This study aims to analyze the characteristics and factors that influence the decisions of the millennial and zillennial generations towards ownership of Hajj savings in West Java. Respondents in this study are millennials and zillennials who already have Hajj savings in West Java. This study uses primary data from 200 respondents. The results of the SEM-PLS analysis show that in the millennial generation the variables of cost and motivation have a significant positive effect, while in the zillennial generation the variables of motivation and trust have a significant positive effect.